Yesus: Tuhan, Guru dan Teladan Orang Percaya - Stephanus Hartoyo (Sekolah Tinggi Theologia Nazarene Indonesia, 2016)
Education is so important and it has indeed given uncountable contributions upon the development of our world as well as our lives. Through education we are able to equip our children and younger generation with necessary information and skill so that they are ready to face the future. In term of Christian education and spiritual formation, we need to fix our eyes on Jesus. Jesus is Lord, to whom we give our lives and services. He is also our teacher, to whom we learn the truth and implement it in our daily lives. The most important, however, is to follow his example, his humbleness and sincerity. In most cases, when we are talking about education, we have seen numerous talented teachers, but many of them are not able to be good examples. Briefly, a teacher must be able to bring light into the darkness, but also to guide the learners on the right path.